History of the China’s Case Guidance System and Judicial Reform - Tang, Mengling (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
This thesis delineates the history of the development of the Case Guidance System (CGS) by combing through the Work Reports of the Supreme People's Court (SPC) since 1980 and specific legal norms on case guidance work. The development of the CGS in China can be divided into five periods: (1)From 1949 to 1978, when cases typically presented social conflicts and served as materials for law-making. (2)From 1978 to 1985, it was for interpreting statutes. (3)From 1985 to 2003, both judicial interpretation and cases were imperative and formed the “two-leg way” for law application. This period witnessed the exploration of the openness of the judicial trail. (4)From 2004 to 2018, there was a strong emphasis on the construction of the cases guidance system, and normative documents were formulated and issued. (5)From 2020 to 2023, the Retrieval of Similar Cases emerged and expend to consider other non-guiding cases to be used. The development of the CGS in China has three characteristics: (1)It has undergone a transformation from being a source of materials for law-making to a tool for the uniform application of laws, rather than a source of laws. (2)It possesses the function of publicizing the rule of law to citizens. (3)The Guiding Gases issued by the SPC have highly binding force, but the other non-guiding cases gradually be emphasized and could be considered in the trail, which means the scope of cases have expended and the new platform is forming.